Computer Devices Changing the Concept of Property Larceny Crime (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, by author considered and analyzed the crime of larceny of property by using a computer and noted to differ this type of crime from other types of theft and similar crimes in the IT sphere in terms of the object and the objective side, and the subject and the subjective side of the corpus delicti. Moreover, author mentioned, while studying the corpus delicti of a certain crime, a detailed analysis of its objective features allows drawing conclusions that are more precise. However, in the article there are some suggestions and recommendations to improve the mechanism in this area.